Molecular interaction between plants and Trichoderma species against soil-borne plant pathogens - Dutta, Pranab; Mahanta, Madhusmita; Singh, Soibam Basanta; Thakuria, Dwipendra; Deb, Lipa; Kumari, Arti; Upamanya, Gunadhya K.; Boruah, Sarodee; Dey, Utpal; Mishra, A. K.; Vanlaltani, Lydia; VijayReddy, Dumpapenchala; et al. (Frontiers in Plant Science, 2023)
Trichoderma spp. (Hypocreales) are used worldwide as a lucrative biocontrol agent. The interactions of Trichoderma spp. with host plants and pathogens at a molecular level are important in understanding the various mechanisms adopted by the fungus to attain a close relationship with their plant host through superior antifungal/antimicrobial activity. When working in synchrony, mycoparasitism, antibiosis, competition, and the induction of a systemic acquired resistance (SAR)-like response are considered key factors in deciding the biocontrol potential of Trichoderma. Sucrose-rich root exudates of the host plant attract Trichoderma. The soluble secretome of Trichoderma plays a significant role in attachment to and penetration and colonization of plant roots, as well as modulating the mycoparasitic and antibiosis activity of Trichoderma. This review aims to gather information on how Trichoderma interacts with host plants and its role as a biocontrol agent of soil-borne phytopathogens, and to give a comprehensive account of the diverse molecular aspects of this interaction.